Revelando os modos de vida da Ponta do Tubarão - Nobre, Itamar de Morais (2005)
It is analyzed the social struggle held by locals at Barreiras, Diogo Lopes and Sertãozinho communities (Macau-RN) in order to avoid the ownership of its mangrove area to hotel managers, in 1995 and to hinder the destruction of Ilha dos Cavalos mangrove by the shrimp producers, in 2000, what led to the creation of Ponta do Tubarão Reserve of State Sustainable Development, located at Macau and Guamaré cities, northern coast of Rio Grande do Norte, respectively 180 and 200 kilometers away from Natal, created in July, 18, 2003 by the Decree State Law n. 8.349, to preserve its traditional territory and way of life. It is photographed and analyzed the developed ways of life in this Unit of Conservation, from the sociocultural category, based in pointers of the material production in the life ways as: the work, the leisure, the religion, the popular knowledge and the action of the contemporary men on the environment. In this perspective, it is considered as method strategy a sociocultural photo cartography, created to this research, and to be concretized used photographic documents, observation, interviews, documental research and bibliographic research, being an association of techniques as peculiarities of this strategy of research. It is concluded that the social struggle developed by the collective actors at Ponta do Tubarão Reserve of State Sustainable Development, is characterized as a transforming action against the global and predatory capital, for the maintenance of the environment and the traditional way of life; One also concludes that the sociocultural photo cartography is very important as a proposal of possible procedures to being used in qualitative researches, because of its analytical potentialities providing a more including vision of the sociocultural routine of the studied space, in the attempt to know and to disclose the relations lived for the citizens of the research in Social Sciences